2023
DOI: 10.1088/1402-4896/acd0e3
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of different metals doped α-PbO nanoparticles for photocatalytic degradation of Methylene Blue dye

Abstract: In recent days, metallic oxide semiconductor nanoparticles have drawn attention to the photocatalytic degradation of organic pollutants. In the present work, undoped and different metals (Sn, Co, Cu, Ni, and Li)-doped of α-PbO nanoparticles were successfully synthesized by a facile chemical precipitations method. The obtained nanoparticles were further studied by using different characterization techniques. The XRD results confirmed that the prepared nanoparticles were a tetragonal, α-PbO phase crystal structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…The literature has reported that the undoped/dopant surface could act as regulation sites for separating photoinduced electron-hole pairs and improves photocatalytic performance [18]. Our group recently reported the influence of various metal-doped α-PbO catalysts for the photodegradation of MB dye under visible light irradiation [19]. The results obtained confirmed the significant influence of fabrication methods on the tuning of photocatalyst properties.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…The literature has reported that the undoped/dopant surface could act as regulation sites for separating photoinduced electron-hole pairs and improves photocatalytic performance [18]. Our group recently reported the influence of various metal-doped α-PbO catalysts for the photodegradation of MB dye under visible light irradiation [19]. The results obtained confirmed the significant influence of fabrication methods on the tuning of photocatalyst properties.…”
Section: Introductionsupporting
confidence: 67%
“…In this study, pristine and metal-doped β-PbO nanoparticles (NPs) were synthesized following the method outlined in [19]. For pristine β-PbO, 50 ml of distilled water and 0.5 M Pb(CH 3 COO) 2 .3H 2 O were added to a beaker and stirred until a clear solution formed.…”
Section: Preparation Of Pristine and Metals Doped β-Pbo Npsmentioning
confidence: 99%
“…Apart from that, black-phosphorus-analog lead monoxide (PbO) is also of research interest in recent years owing to its excellent photodetection and nonlinear optical properties [ 15 , 16 , 17 , 18 , 19 , 20 ]. PbO is a layer compound which exists in two crystal forms: red tetragonal (α) and yellow orthorhombic (β) forms [ 21 ], both of which have been experimentally synthesized [ 20 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%